Memahami Surat An-Nisa Ayat 59 Melalui Problem Based Learning - Nuri, Rafika (MGMP PAI SMP BINTAN, 2024)
The aim of this research is to determine the effect of the problem based learning method on improving the learning outcomes of class VII students at SMPN 28 Bintan. This type of research is Classroom Action Research (PTK). Data collection techniques use observation, tests and documentation. The research design used is Classroom Action Research with two research cycles. The research subjects were all Class VII B students of SMPN 28 BINTAN for the 2022-2023 academic year, totaling 17 people. The data analysis technique uses the formula for average value, percentage of learning completeness and observation data. From the research results, it was concluded that the research results showed that after the Classroom Action Research was carried out, students' grades experienced positive changes compared to before the action took place. This research contributes to the learning process, especially Islamic Religious Education and other subjects in general.